Conflict Mediation, Emotional Regulation and Coping Strategies in the Educational Field - Bonilla R., Pedro; Armadans, Immaculada; Anguera, M. Teresa (Frontiers in Education, 2020)
Conflict mediation, emotional regulation and coping strategies in the educational field. Conceptual analysis Pedro Bonilla¹ ̽, Imma Armadans², M. Teresa Anguera2 ¹ UNED. San José, Costa Rica, ², Department of Social Psychology and Quantitative Psychology, University of Barcelona, Barcelona, Spain *Correspondence Pedro Bonilla pbonilla@uned.ac.cr Abstract Teachers who present high emotional skills and knowledge of strategies to mediate the conflicts generated in the classroom, are able to exercise a better management of both the teaching tasks that correspond to them and to establish an emotionally nutritive and productive educational climate for the students. This research aims to study and analyze, under an integrative conceptual revision methodology, the theories and models that consider individual, group and social aspects of the origin, development and attention of conflicts, as well as emotional elements that underlie people’s behavior. All this within interpersonal relationships and in the different areas of action; in order to synthesize the results of each, establishing points of agreement and complementarity that serve to be adapted to the educational field. Educational mediation and emotional regulation are two constructs that have been previously studied separately, or in conjunction with others, but not in a complementary way between them. The presentation of these conceptual discussions suggests the formulation of new theoretical proposals, aimed at improving interpersonal relationships, the environment and dynamics of teaching-learning, focusing efforts on the teachers' collective. Descriptors: Emotional Regulation, Educational Mediation, Teachers, Conflicts, Interpersonal Relations